"Geografia otwarta” Obraz wyśnionego miejsca w wierszach Wojciecha Śmigielskiego - Szott, Mirosława (In Gremium. Studies in History, Culture and Politics, 2016)
„The Open Geography”. The representation of a dream place in the poetry of Wojciech Śmigielski The open geography of Wojciech Śmigielski is the geography not requiring maps, deprived of the Lubusz context, though growing out of and nominally adjacent to it. The place is depicted in different ways in the texts of Lubusz poets. Some of them emphasise its naturalness, others impose on it imaginative nets of the remote areas they had to leave in the past, still for others these are the historical or sociological aspects that appear important. Śmigielski decided to introduce another way of constructing the space. He chose a universal and, at the same time, unreal styling. The poems from “The Breath” show the attempt to make the place meaningful through including fairy-tale and dream-like motifs. The text shows the way it translates into a representation of space in the works of the poet. Is Droniki – a village Śmigielski lived in – a mirror image of the real Droniki? In this article, I also check whether the psychoanalytic tools can be used to analyse this poetry.